2022
DOI: 10.1007/s00066-022-01941-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a ketogenic diet intervention during radiotherapy on body composition: V. Final results of the KETOCOMP study for head and neck cancer patients

Abstract: Purpose Patients with head and neck cancer (HNC) are at risk of malnutrition, especially during radiochemotherapy. We aimed to study the impact of a ketogenic diet (KD) versus an unspecified standard diet (SD) on body composition and survival in HNC patients undergoing radio(chemo)therapy. Methods As part of a controlled clinical trial, non-metastasized HNC patients were enrolled into either a KD ( N = 11) or an SD ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In addition, radiotherapy is the mainstay of anti-tumor treatment, which can significantly improve the survival rate of cancer patients. Study had reported that KD preserved fat free and skeletal muscle mass and effectively improved global quality of life in breast cancer patients undergoing curative radiotherapy ( 13 ); it also partially counteracted the adverse effects of radiotherapy on body composition in head and neck cancer patients ( 42 ). Importantly, the cluster of keywords showed that immunotherapy is the new hotspot in this field recently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, radiotherapy is the mainstay of anti-tumor treatment, which can significantly improve the survival rate of cancer patients. Study had reported that KD preserved fat free and skeletal muscle mass and effectively improved global quality of life in breast cancer patients undergoing curative radiotherapy ( 13 ); it also partially counteracted the adverse effects of radiotherapy on body composition in head and neck cancer patients ( 42 ). Importantly, the cluster of keywords showed that immunotherapy is the new hotspot in this field recently.…”
Section: Discussionmentioning
confidence: 99%
“…The KD has so far only been found to reduce the negative effects of treatment on body weight and body composition, with no significant effects on the patient survival. [53,54] The ACS recommends that HNC survivors adopt a diet high in vegetables, fruits, and whole grains; low in saturated fat; adequate in dietary fiber; and alcohol-free. [55] Therefore, the use of the KD should be carefully considered for patients with HNC.…”
Section: Nutritional Formulasmentioning
confidence: 99%
“…Thus, fatty acids become the required obligatory source of cellular energy and target the Warburg Effect in highly glycolytic tumors. (Klement & Sweeney, 2022;Voss et al, 2022;Woolf et al, 2016) The clinical trials describe KD and IFʹs role in brain cancer, non-metastasized rectal cancer, highgrade glioma (new and recurrent), head and neck squamous cell carcinoma, locally advanced and metastatic breast cancer, and ovarian and endometrial cancer. (Augustus et al, 2021;Cohen et al, 2020;Khodabakhshi et al, 2020Khodabakhshi et al, , 2021Klement, Koebrunner, et al, 2021;Klement, Weigel, et al, 2021;Klement & Sweeney, 2022;Ma et al, 2021;Porper et al, 2021;Voss et al, 2022) Results of these studies described KD as accompanying measure for cancer patients undergoing standard-of-care therapy that helps to improve the quality of life, survival with no severe side effects, and acceptable safety and tolerability in advanced cancer patients.…”
Section: Role Of Kd and If In Cancersmentioning
confidence: 99%